Preserving the Saudi Monarchy Political Pragmatism in Saudi Arabia, c.1973-1979 - Willner, Samuel E. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book provides a new perspective on the study of the Kingdom of Saudi Arabia and its monarchy - its political leadership and decisions. Moreover, it analyzes how that decision-making evolved before, during, and after the Arab-Israeli War of 1973, and the subsequent Arab oil embargo that followed; the run-up to and aftermath of the 1975 murder of King Faysal; discussions over the oil weapon; and Saudi responses to the Carter presidency in the United States. Through the prism of tribal decision-making, this book sheds new light on a number of important political events, which have shaped the political leadership in Saudi Arabia, and explores the behind-the-scenes workings of the Saudi royal family. Samuel Willner is Research Fellow at the University of Haifa, Israel.
1.Introduction -- PART I: THE FOUNDATIONS OF POLITICAL LEADERSHIP IN SAUDI ARABIA -- 2. Tribal decision-making: From traditional to modern context -- 3. Central characteristics of Saudi foreign policy -- PART II: THE 1973 ARAB-ISRAELI WAR AND THE ARAB OIL EMBARGO -- 4. Emerging pan-Arabism and the politicization of Arab oil -- 5. Conflicting interests and King Faysal's decision to support Egypt's war efforts -- PART III: THE END OF THE OIL EMBARGO AND THE MURDER OF KING FAYSAL -- 6. Towards the end of the oil embargo -- 7. Faysal's threats of a new oil embargo -- 8. The murder of King Faysal -- 9. The top-secret Saudi plan to use the USSR to pressure the US -- PART IV: THE SURVIVAL OF THE SAUDI MONARCHY DURING THE CARTER ADMINSTRATION (1977-1981) -- 10. Saudi concerns of the Marxist and Arab revolutionary threats (1977-1978) -- 11. The 1978-1979 Islamic Revolution in Iran -- 12. Inspired by the Islamic Revolution: Rebellions, uprisings and coup attempts -- 13. Saudi, CIA messages to President Carter: A US policy-change towards the Saudis is necessary -- 14. Final Conclusions.
Keywords: Asia -- History; United States -- History; World politics; History, Modern; Middle East -- Politics and government; Asian History; US History; Political History; Modern History; Middle Eastern Politics